Basic life support in Intensive Care Unit: integrative review on the knowledge produced in nursing (Research, Society and Development, 2022)
This study aimed to synthesize information on the production of knowledge in nursing on basic life support in Intensive Care Units. This is an integrative literature review. The method proposed by Ganong was adopted. The PICo strategy was used to elaborate the guiding question: “What is the production of knowledge in nursing about basic life support in the ICU?”. After applying the inclusion and exclusion criteria and analyzing the studies, 5 articles were included to compose this review that answered the guiding question. The following topics were highlighted for discussion: profile of CRA patients in the ICU, the knowledge of the ICU nursing on BLS, and the ICU as a place for post-CRA care. The nursing team must keep constantly updated on the technical standards and practices recommended by the AHA, as well as knowing the profile of patients who develop CRA. The post-CRA environment must be properly equipped so that the patient is better monitored and their evolution accompanied.